Healthy BIM: the feasibility of integrating architecture health indicators using a building information model (BIM) computer system. (18th December 2020) - Rice, Louis
Abstract : Purpose: The COVID-19 pandemic has forced billions of people into lockdown; foregrounding the important relationship between architecture and health. In this context, there is heightened urgency for the construction sector to improve the healthiness of buildings. Accordingly, the research identifies the feasibility of measuring various building health indicators (BHIs) through the use of a building information management (BIM) model. The research seeks to find optimal strategies for integrating the near ubiquitous use of BIM with a range of health indicators related to building design. Design/methodology/approach: A systematic literature review was undertaken to identify potential BHIs for use in BIM models. The research then undertook a Delphi technique in order to test the hypothesis. In total, three rounds of questionnaire-based surveys were undertaken with expert participants. Findings: The research identifies three different levels of BIM complexity in order to achieve the integration of health indicators. The most simple strategy suggests BHI can be directly measured using existing BIM models; the next level of sophistication requires "plug-in" software to BIM models; the final level would require additional sensors and detectors in a "smart" building. Practical implications: The research is significant for users of BIM, building designers, public health advisors, construction professionals, healthcare providers, social prescribers, architects and clients. Originality/value: The integration of BHI into the architectural design process is an important step towards the construction sector improving health and well-being. The research provides for the first time a rigorous identification of the most viable mechanisms through which BIM may be used to measure the healthiness of a building.